Barrier-to-autointegration-factor (Banf1) modulates DNA double-strand break repair pathway choice via regulation of DNA-dependent kinase (DNA-PK) activity - Burgess, Joshua T (Nucleic Acids Res, 2021)
DNA repair pathways are essential to maintain the integrity of the genome and prevent cell death and tumourigenesis. Here, we show that the Barrier-to-Autointegration Factor (Banf1) protein has a role in the repair of DNA double-strand breaks. Banf1 is characterized as a nuclear envelope protein and mutations in Banf1 are associated with the severe premature aging syndrome, Néstor–Guillermo Progeria Syndrome. We have previously shown that Banf1 directly regulates the activity of PARP1 in the repair of oxidative DNA lesions. Here, we show that Banf1 also has a role in modulating DNA double-strand break repair through regulation of the DNA-dependent Protein Kinase catalytic subunit, DNA-PKcs. Specifically, we demonstrate that Banf1 relocalizes from the nuclear envelope to sites of DNA double-strand breaks. We also show that Banf1 can bind to and directly inhibit the activity of DNA-PKcs. Supporting this, cellular depletion of Banf1 leads to an increase in non-homologous end-joining and a decrease in homologous recombination, which our data suggest is likely due to unrestrained DNA-PKcs activity. Overall, this study identifies how Banf1 regulates double-strand break repair pathway choice by modulating DNA-PKcs activity to control genome stability within the cell.